PERFORMA KUALITATIF KAMBING RAMBON BETINA PASCASAPIH (STUDI KASUS DI DUSUN V DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN) - Rolin Gita Saputra; Arif Qisthon; Muhammad Dima Iqbal Hamdani; Akhmad Dakhlan (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study aimed to determine the qualitative performance of female Rambon goat (Ettawa Grade x Kacang goat) at post-weaning. This reaserch was conducted in January - February 2020 in Dusun V of Sungai Langka village, Gedong Tataan district, Pesawaran regency, Lampung. The research used a survey method with case study in Dusun V of Sungai Langka village, Gedong Tataan district, Pesawaran regency, Lampung. Observation on the qualitative performance of Rambon goat at post-weaning aged 4 months to 1 year included the color of head, the color of the body, the color of legs, the color of the tail, the color of ears, head shape, body shape, ears shape, ayes shape, face shape, face profile, availability of tail hair or not, and the shape of the horns of the goat. Rambon goats used in this study were 47 female goats at post-weaning age. The results of this research showed that qualitative performance of post-weaning female Rambon goat in Sungai Langka village, Gedong Tataan district, Pesawaran regency were more similar to those of Ettawa Grade goat (PE goat) compared to those of Kacang goat. Key Words: Rambon goat, Qualitative performance, Post-weaning